Cyber Security Act 2024: a facelift to the cyber security in Malaysia - Zulhuda, Sonny (Selcuk University, Turkiye, 2025)
Digitalization has permeated all aspects of life, with many critical activities now dependent on digital systems. The World Economic Forum report highlighted technological risks as a key global concern, including widespread cybercrime, critical infrastructure breakdown, digital inequality, and adverse outcomes of new technologies. Weak cybersecurity infrastructure exacerbates these issues, potentially leading to misinformation, social cohesion erosion, supply chain collapse, and even social conflicts. Therefore, strengthening cybersecurity policies is crucial for addressing these challenges and ensuring a resilient digital future. With so many stories of cyber threats and cyber attack incidents, Malaysian lawmakers brought this issue to the primary stage of policy-making by introducing the Cyber Security Act 2024 [Act 854]. The Act was first passed by the House of Representatives on 27th March 2024 and was gazetted on 26th June 2024. The Act is meant to enhance national cyber security by providing for the establishment of the National Cyber Security Committee, duties and powers of the Chief Executive of the National Cyber Security Agency, functions and duties of the national critical information infrastructure sector leads and national critical information infrastructure entities and the management of cyber security threats and cyber security incidents to national critical information infrastructures, to regulate the cyber security service providers through licensing, and to provide for related matters.